2008
DOI: 10.4049/jimmunol.180.3.1598
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cells License Adult CD34+ Hemopoietic Progenitor Cells to Differentiate into Regulatory Dendritic Cells through Activation of the Notch Pathway

Abstract: The mechanisms underlying the immunomodulatory functions of mesenchymal stem cells (MSC) on dendritic cells (DC) have been shown to involve soluble factors, such as IL-6 or TGF-β, or cell-cell contact, or both depending on the report referenced. In this study, we intend to clarify these mechanisms by examining the immunosuppressive effect of human adult MSC on adult DC differentiated from CD34+ hemopoietic progenitor cells (HPC). MSC have been shown to inhibit interstitial DC differentiation from monocytes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
185
3
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 227 publications
(201 citation statements)
references
References 36 publications
10
185
3
3
Order By: Relevance
“…However, although we do not have direct evidence, our data are compatible with a contact-dependent mechanism of suppression, perhaps mediated by an intermediate mediator linking the MSCs to Treg induction. In this respect, Li et al recently showed that Treg-inducing dendritic cells can be generated through direct cell-to-cell contact between haematopoietic stem cells and MSCs by activation of the Notch signalling pathway [30]. Whether a similar mechanism is at play in our model requires further investigation.…”
Section: Discussionmentioning
confidence: 80%
“…However, although we do not have direct evidence, our data are compatible with a contact-dependent mechanism of suppression, perhaps mediated by an intermediate mediator linking the MSCs to Treg induction. In this respect, Li et al recently showed that Treg-inducing dendritic cells can be generated through direct cell-to-cell contact between haematopoietic stem cells and MSCs by activation of the Notch signalling pathway [30]. Whether a similar mechanism is at play in our model requires further investigation.…”
Section: Discussionmentioning
confidence: 80%
“…Indeed, BM-MSCs were found to directly induce CD4 and CD8 Treg cell functions (35,36). Alternatively, some studies have suggested that BM-MSCs could alter the differentiation and activation of dendritic cells, inducing the generation of dendritic cells with tolerogenic functions (37,38). Whether human AD-MSCs share this capacity with BM-MSCs is still unknown, but the generation of Treg 1016 GONZÁ LEZ ET AL cells by human AD-MSCs through the induction of tolerogenic dendritic cells emerges as an attractive mechanism that needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In humans and rodents, MSCs also modulate DC maturation, differentiation and function [42,50,51]. To date, there are no reports of MSC interaction with equine DCs.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…This transition is critical for mounting an immune response because immature DCs fail to prime T cells effectively but induce tolerance rather than immune rejection. MSCs appear to keep DCs in an immature state [51] and inhibit the maturation of myeloid-DCs and plasmocytoid-DCs [42].…”
Section: Dendritic Cellsmentioning
confidence: 99%
See 1 more Smart Citation